Exploring the processes of change facilitated by musical activities on mental wellness. Issue 2 (15th March 2018) - Kwan, Chi Kin; Clift, Stephen
ABSTRACT: While the benefits of music to people's mental health have long been recognized, the process of how it works requires further investigation. This paper is based on the results of a community-based music project offered to a group of mental health service users by a Hong Kong social service centre. A six-dimensional framework, which contains emotional, psychological, social, cognitive, behavioural and spiritual dimensions, is constructed for understanding how musical activities may produce benefits for mental health service users. Through conducting 23 interview sessions with the participants (N = 47) this study examines the processes of change within musical activities. The participants suffered from mental health problems including mood disorders, anxiety disorders, schizophrenia and other psychotic disorders. Feedback was solicited from them by listening to their first-hand experiences as service users of the musical activities. Recorded interviews were transcribed and analysed to generate themes that correspond to the six dimensions the researchers proposed. This study shows that the clinical effects elicited by the musical activities described fit closely with the needs of mental health service users. Its findings suggest that community-based musical activities have clear potential for supporting mental health service users in recovery, which deserve further promotion.